Effect of pro-oxidants on the photodegradability of recycled PE films containing calcium carbonate - Nguyen, Thanh Tung; Pham, Thu Trang; Nguyen, Van Khoi; Pham Thi, Thu Ha; Nguyen, Trung Duc (Vietnam Journal of Science and Technology, 2025)
In this study, calcium carbonate (CaCO3) filled waste high density polyethylene (HDPE) fims without and with prooxidants were prepared using a twin screw extruder. To control the degradation time, the HDPE film with prooxidants content varying from 0.5 – 2 wt. %, 25 wt % taical and 0.5% antioxidant additive were investigated. The mechanical properties, Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC) and scanning electron microscope (SEM) were used to assess the changes of films during accelerated weathering according to ASTM G154 standard (340 nm UV lamp, 8 hours UV, 4 hours condensation at 50 oC). The results showed that the degradation rate of HDPE increased by increasing of prooxidant content. After 6 days of accelerated weathering, FTIR spectra of oxidized HDPE films showed peaks of OH, C-O, C-O-C, C=O groups. The melting point decreased and the heat of fusion increased as the content of prooxidants increased.